The Influence of Organizational Culture on Employee Performance at the Gorontalo City Transportation Office - Lutfiya Tangahu; Rusli Isa; Romy Tantu (Public Policy Journal, 2025)
This study aims to find out how Organizational Culture Affects Employee Performance at the Gorontalo City Transportation Office. Data collection is carried out by Observation, Documentation, and Questionnaire which is distributed to employees working at the Gorontalo City Transportation Office. Data analysis was carried out using a quantitative method, namely to test the influence of independent variables and bound variables. The data analysis technique uses simple linear regression analysis. The results of this study show that based on the results of a simple regression test, there is an influence between variable X (Organizational Culture) and variable Y (Employee Performance). The coefficient has a significant positive value, which means that the organizational culture variable has an effect on the employee performance variable, which is 0.283. The constant value is 63,801, if there is no organizational culture value, then the employee performance value is 63,801. For every one percent increase in organizational culture, the employee performance value increases by 0.283. The coefficient has a positive value that if the organizational culture increases, the employee performance increases, and from the results of the determination coefficient test shows that the influence of organizational culture variables is 41.8%. This is evidenced by the determination coefficient test, which is with an R value of 0.418, meaning that the overall organizational culture variable has an influence of 41.8% on the employee performance variable. While the remaining 58.2% was influenced by other variables that were not studied in this study. Therefore, for the next researcher to be able to add other independent variables that are not included in this study